Developing, Integrating, and Implementing Evidence-Informed Practice Curricula Throughout a Chinese Medicine Degree Program - Anderson, Belinda J. (J Altern Complement Med, 2020)
Objectives: To train faculty and develop curricula in evidence-informed practice (EIP) within a Chinese medicine degree program. Setting: Pacific College of Oriental Medicine (New York). Design: Faculty EIP training was undertaken through utilization of online EIP modules, and development and completion of a 3-credit (45 h) online Foundations of EIP course. This was supplemented by faculty meetings and one-on-one support from department chairs. Curriculum development was undertaken by an EIP Curriculum Committee. The committee followed a modified Delphi process to develop EIP course learning outcomes (CLOs), and to make changes to the College's clinic policies and procedures. EIP assignments were developed for each course in accordance with the CLO. Results: Ninety-one percent of the faculty and 97% of clinical supervisors received formal EIP training. Thirty-five percent of all didactic faculty, 38% of faculty teaching courses with EIP incorporated, and 30% of clinical supervisors completed 10 or more h of EIP training during this project. Faculty also received informal EIP training through participation in department and general faculty meetings. Seventy-three percent of the Master's degree curriculum, inclusive of 40 didactic courses and fifteen 60-h clinic shifts, were modified to incorporate EIP. EIP CLOs and corresponding assignments were developed. Clinic intake forms were modified to facilitate undertaking EIP in the College clinic. Issues related to how EIP is defined in conjunction with the nature of available scientific research in Chinese medicine required discussion and resolution. Conclusions: Training faculty and developing curricula in EIP within Chinese medicine colleges has unique challenges that must be factored into the strategies and processes. Factors that contributed to the success of this project were having faculty drive the process, integrating EIP content within existing curricula, gradual exposure, identifying champions, relating EIP to practice building, and openly discussing opposing perspectives.